Interpreting the Solution Architect’s Role at a leading IT and Consultancy Company - Magalhães, Pedro Miguel Faria (2013)
At the end of the twentieth century, an individual or a small company could design and develop an application or even some bigger and scalable systems. However, due to their increasing complexity, project size and required higher levels of integration, the need for new roles and processes associated with software development drastically increased, calling for skills to assure the integrity and effectiveness of solutions. A new role, called “Solution Architect”, emerged over time and has been formally used in leading companies such as Cisco, IBM, Microsoft, Oracle and SAP, but it is still lacking agreement on its scope and responsibilities. Having the retail sector as the context in which a leading IT and consultancy company operates, this research builds upon the experience of seven Solution Architects from a pool of fourteen inquiring them on their perceptions about their roles in order to better understand the required skills and boundaries of this new role against more established architectural roles. At the end of this research, it was clear that the interpretations of this role’s span across a project’s lifecycle as well as the boundaries to other roles such as the Enterprise Architect’s one were not the same. Nevertheless, the consultancy side of the Solution Architect role gathered the most consensuses as opposed to the more traditional technical side, which wasn’t selected by any Solution Architect. Anyway, the scope dilemma still persists within a project leading to a role overlap between Enterprise and Solution Architect.